Temperature‐driven directional coalescence of silver nanoparticles. (1st April 2016) - Yan, Shi; Sun, Dongbai; Gong, Yu; Tan, Yuanyuan; Xing, Xueqing; Mo, Guang; Chen, Zhongjun; Cai, Quan; Li, Zhihong; Yu, Hongying; Wu, Zhonghua
Abstract : A four‐stage model for the sintering process of PVP‐coated silver nanoparticles is described. Abstract : Silver nanoparticles were synthesized with a chemical reduction method in the presence of polyvinylpyrrolidone as stabilizing agent. The thermal stability behavior of the silver nanoparticles was studied in the temperature range from 25 to 700°C. Thermal gravimetric analysis was used to measure the weight loss of the silver nanoparticles. Scanning electron microscopy and high‐resolution transmission electron microscopy were used to observe the morphology and the change in shape of the silver nanoparticles. In situ temperature‐dependent small‐angle X‐ray scattering was used to detect the increase in particle size with temperature. In situ temperature‐dependent X‐ray diffraction was used to characterize the increase in nanocrystal size and the thermal expansion coefficient. The results demonstrate that sequential slow and fast Ostward ripening are the main methods of nanoparticle growth at lower temperatures (<500°C), whereas successive random and directional coalescences are the main methods of nanoparticle growth at higher temperatures (>500°C). A four‐stage model can be used to describe the whole sintering process. The thermal expansion coefficient (2.8 × 10 −5 K −1 ) of silver nanoparticles is about 30% larger than that of bulk silver. To our knowledge, the temperature‐driven directional coalescence of silver nanocrystals is reported for the first time. Two possible mechanisms of directional coalescence have been proposed. This study is of importance not only in terms of its fundamental academic interest but also in terms of the thermal stability of silver nanoparticles.